2012
DOI: 10.1134/s1070363212010069
|View full text |Cite
|
Sign up to set email alerts
|

Liquid extraction of some rare earth elements with aminomethylphosphine oxides

Abstract: Methods were developed of the solvent extraction from aqueous solutions of hydrochloric, nitric, and perchloric acids of the triply charged ions of rare earth elements including samarium, lutetium, dysprosium, neodymium, and ytterbium, using as reagents the lipophilic aminomethylphosphine oxides containing two or four dialkylphosphinyl groups, and toluene, chloroform, and methylene chloride as the organic media. The study of the effect of concentration of mineral acids on the degree of metal extraction showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…We followed research in this direction studying the properties of previously unknown acetal containing the aminophosphine oxide fragment. Aminophosphine oxide derivatives are used as alkali and rare metal extractants due to their ability to complexation . A combination of several functional groups in one molecule (acetal and secondary amino group) would allow the use of the compounds of this type as a universal synthetic block for the design of macrocyclic and linear polyphenols, promising polydentate ligands containing the phosphine oxide fragment.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…We followed research in this direction studying the properties of previously unknown acetal containing the aminophosphine oxide fragment. Aminophosphine oxide derivatives are used as alkali and rare metal extractants due to their ability to complexation . A combination of several functional groups in one molecule (acetal and secondary amino group) would allow the use of the compounds of this type as a universal synthetic block for the design of macrocyclic and linear polyphenols, promising polydentate ligands containing the phosphine oxide fragment.…”
Section: Introductionmentioning
confidence: 80%
“…It was shown earlier that calix[4]arenes containing aminophosphonate fragments on the upper rim of molecule are effective and selective amino acid transfer agents compared with their linear counterparts and lipophilic derivatives of aminophosphine oxides participate both in membrane transport of amino acids and as metal ion extractants from acidic media . It is anticipated that the presence of lipophilic cavity with a long alkyl chain and four thermally and hydrolytically stable aminophosphine oxide fragments in synthesized calix[4]resorcinol would increase the binding efficiency and selectivity with organic and inorganic substrates compared with their linear counterparts and unsubstituted calix[4]resorcinol.…”
Section: Resultsmentioning
confidence: 99%
“…Because the syntheses of 29 and 31 were challenging, their extraction studies were only carried out in perchloric acid containing Lu( iii ). Cherkasov et al found out that the extraction efficiency of the synthesized extractants strongly depended on the nature of the acidic solution [ 36 ]. The extraction efficiencies of 29 and 31 were comparable with 22 in perchloric acid.…”
Section: The Short History Of α-Aminophosphonates -Phosphinates and -...mentioning
confidence: 99%
“…α-Aminophosphonates 8 – 14 together with α-aminophosphinate 21 and α-aminophosphine oxides 22 – 32 were synthesized using the same procedure, by refluxing the reagents either in benzene, toluene, or acetonitrile and using p -toluenesulfonic acid as the acid catalyst [ 11 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 50 , 51 ]. The progress of the reaction was monitored by measuring the amount of water formed into the Dean–Stark trap.…”
Section: Synthesis Of α-Aminophosphonates -Phosphinates and -Phosphin...mentioning
confidence: 99%
“…There are a number of efficient reagents used for metal extraction, most notably organophosphorus compounds [13][14][15][16][17][18][19][20][21][22][23] and amines [24]. The synergistic extraction of these divalent transition metal ions with mixtures of neutral organophosphorus extractants and amine extractants has been reported previously [25].…”
Section: Introductionmentioning
confidence: 99%